Performance Indicators of Business Subjects: World Experience and Development - Saodat Arislanovna Yuldasheva (Global Scientific Publishing, 2022)
the article analyzes some indicators of the functioning of business entities in various countries. The experience of highly developed countries of the world is studied, the features of small business development in developing countries are highlighted. The results of the study constitute a theoretical basis for the formation of a methodological framework, from which it follows that the creation of small enterprises is possible in two ways: self-development and integration development.
Keywords: business; integration development; small business; entrepreneurship